Sicherheit der transkraniellen magnetischen oder elektrischen Hirnstimulation - Paulus, Walter (Klinische Neurophysiologie, 2017)
Sowohl die transkranielle Magnetstimulation (TMS) als auch die transkranielle Gleichstromstimulation (tDCS) gelten als weitgehend sichere Verfahren, wenn die Sicherheitskriterien beachtet werden. Diese werden in diesem Beitrag erläutert sowie auf sonstige Nebenwirkungen der transkraniellen Hirnstimulationsverfahren eingegangen.Both transcranial magnetic (TMS) and transcranial direct current stimulation (tDCS) are widely accepted as safe methods. Epileptic seizures rarely occur with TMS in patients with brain diseases; only with repetitive TMS with too high stimulus frequencies and intensity usually outside the safety criteria do such episodes occur. In 2 othger cases, stimulation of skin receptors may result in perception of tingling or pain locally or in temporary generalized headaches. tDCS can, in rare cases, induce local reversible skin burns when the electrodes are dried out; under proper use, only skin redness or tingling perception under the electrodes is noticed.
Keywords: transkranielle Magnetstimulation; TMS; transkranielle Gleichstromstimulation; tDCS; Sicherheit; Epilepsie